Added value of non-rigid image registration for intrafraction dose accumulation in magnetic resonance imaging-guided prostate radiotherapy - Georgios Tsekas; Cornel Zachiu; Gijsbert H. Bol; Johannes C.J. de Boer; Bas W. Raaymakers (Physics and Imaging in Radiation Oncology)
This work investigates potential advantages of non-rigid versus rigid image registration for intrafraction dose reconstruction in hypofractionated prostate radiotherapy. The data of 15 patients were analyzed using 3D cine magnetic resonance imaging (MRI) in combination with machine log files and the accumulated dose distributions were compared to the planned ones. Both image registration methods resulted in comparable results for the majority ( ∼ 95%) of patient fractions. However, better image alignment was reported for the non-rigid method compared to rigid in cases of transient gas pockets, indicating better image registration quality in the presence of large intrafraction deformations.